Impact of Ground-Based Logging Machine on Soil Physical Properties and Tree Growth - Jusoff, Kamaruzaman (1987)
Five experiments were conducted to determine the impacts of ground-based logging machines on soil physical properties and on early gr01vth of Acacia mangium Willd. The experiments are : (i) a survey of the areal extent of logging machine disturbance, (ii) effects of logging machines on soil physical properties, (iii) effects of travelling intensity with a rubber-tired and track-type logging machine on some soil physical properties, (iv) recovery rate of compacted soils, and (v) measurement of growth responses of A. mangium on compacted and non-compacted soils and their loosening treatments. Areal disturbance on 10 logging blocks following logging with crawler t ractors averaged 30(18), 28(27), and 42(55) percent in 'undisturbed', 'moderate', and 'serious' class of disturbance on clay loam soils in the dry (wet) season, respectively. For sandy loam soils under dry (wet) season, the areal extent of logging disturbance were 16(27), 44(22), and 40(48) percent, respectively. Average values for to penetration, and soil temperature of prelogging soils, adjacent undisturbed soil, secondary forest roads, secondary landings, primary landings and skid trails were also determined.